Solution of optimization tasks by means of Google spreadsheets - Данилевич, Сергей Борисович (Technology audit and production reserves, 2015)
This paper explores the possibility of using free cloud services such as Google Drive to create the economic and mathematical tools to practice their constant use in small and medium business. The main aim of the research is to develop a methodology and best practices for solving optimization problems by means of cloud technologies. Using modern means of communication allow employees collecting and analyzing data without intending to a specific office and computer. This article is an example of creating a virtual template that allows you to quickly calculate the best routes between the cities of Ukraine, which are selected by the user. It is proposed to create in Google spreadsheets like patterns using an arsenal of built-in features, add-ons including the creation of js macros to promptly solve the repetitive business tasks. The research results can be used by managers of small firms engaged in marketing, service of geographically distributed sites and so on.